2019
DOI: 10.1186/s13643-019-1028-2
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing and protective factors influencing suicide ideation, attempt, and death in patients accessing substance use treatment: a systematic review and meta-analysis protocol

Abstract: Background The lifetime risk of suicide in patients with substance use disorder is five to ten times the risk in the general population. Critically, up to 19% of patients continue to think about and attempt suicide even after accessing treatment. Therefore, suicidality represents a significant clinical concern in patients struggling with substance use that warrants careful investigation of the factors involved. While most previous research has relied on limited cross-sectional designs, a growing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…While mood disorders are among the most important risk factors for suicide [ 3 5 ], comorbidity with alcohol and substance use disorders (AUD/SUD) vastly increases vulnerability to suicidal ideation [ 6 , 7 ], attempts [ 8 , 9 ], and deaths [ 5 , 10 , 11 ]. Additionally, suicidal ideation and behavior are significant clinical concerns among those seeking treatment for AUD/SUD [ 12 ], and risk for highly lethal suicide attempts remains to be elevated even after remission from SUD [ 13 ]. While all substances elevate the risk for suicidal behavior, alcohol and opioids are the most common substances identified in suicide decedents (22% and 20%, respectively), far above rates of marijuana (10.2%), cocaine (4.6%), and amphetamines (3.4%) [ 14 •].…”
Section: Introductionmentioning
confidence: 99%
“…While mood disorders are among the most important risk factors for suicide [ 3 5 ], comorbidity with alcohol and substance use disorders (AUD/SUD) vastly increases vulnerability to suicidal ideation [ 6 , 7 ], attempts [ 8 , 9 ], and deaths [ 5 , 10 , 11 ]. Additionally, suicidal ideation and behavior are significant clinical concerns among those seeking treatment for AUD/SUD [ 12 ], and risk for highly lethal suicide attempts remains to be elevated even after remission from SUD [ 13 ]. While all substances elevate the risk for suicidal behavior, alcohol and opioids are the most common substances identified in suicide decedents (22% and 20%, respectively), far above rates of marijuana (10.2%), cocaine (4.6%), and amphetamines (3.4%) [ 14 •].…”
Section: Introductionmentioning
confidence: 99%
“…In a Canadian study, Espinet et al (2019) found that the lifetime suicide risk for individuals with substance use disorder was 5 -10 times higher than the 3 -5% risk in the general population; for individuals with alcohol abuse problems, it was is 10 times higher; for those using opiates it was 14 times higher and for those with mixed-drug use it was 17 times higher. In addition, Espinet et al reported that these individuals made multiple suicide attempts.…”
Section: Drug and Alcohol Usementioning
confidence: 95%
“…Given the unique vulnerabilities of patients with pain conditions and complex interactions of predisposing and enabling factors in this population, suicide prediction models (SPMs) may be effective tools to identify patients at risk and prevent adverse outcomes, including death [ 16 , 17 ]. Although previous SPM studies have shown promising results, few have focused on patients with pain conditions.…”
Section: Introductionmentioning
confidence: 99%